Exchange Rate Movements, Import and Economic Growth in Nigeria (1986-2010) - Oloba, Olusola (International Journal of Business, Economics and Management, 2014)
The study empirically investigates the effect of exchange rate volatility on import trade in Nigeria during the period 1986: 1– 2009: 4. The study focuses on import trade because, the import aspect of trade flows has often been ignored by researchers. The study showed that exchange has been volatile in Nigeria as evident from the unusually high and unusually low standard deviation. Also, the econometric results show that exchange rate displays a clustering trend during the period under investigation which portrays high degree of volatility. Further, the econometric results indicated that a long run relationship exists between exchange rate volatility and trade flows. Also, the study showed a significant negative relationship between domestic output and import component of trade flows suggesting that increasing import tends to shrink production line in Nigeria. The study concluded that exchange rate volatility exerted a significant negative relationship with import in Nigeria.